PERSPEKTIF TINDAK KEJAHATAN KRIMINAL PENGARUH ATAU AKIBAT ALKOHOL - Yeremias Leto, Pankrasius; Hudi Yusuf (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
Alcohol is often used to refer to ethanol, which is also called grain alcohol, and sometimes todrinks that contain alcohol. Ethanol, a compound that has the chemical formula C2H5OH (usually calledethyl alcohol, pure alcohol, or absolute alcohol) is widely used as a solvent for various chemicals intendedfor consumption and other uses, for example in perfumes, flavorings, food colorings, and medicines. Inchemistry, ethanol is an important solvent as well as a feed stock for the synthesis of other chemicalcompounds. Alcohol in human life has dual, conflicting functions. On the one hand, alcohol is a substancethat can help humanity. However, on the other hand, alcohol can be used as a drink which can become avery dangerous boomerang, especially for teenagers. This is because ethanol is used as the basic ingredientin these drinks, not methanol, or other groups of alcohol. Someone who is influenced by alcoholic drinkswill of course find it very difficult to use common sense and their thoughts to control their desires anddesired actions. In this case, the relationship with a crime committed by a person is active, which meansthat a person has no intention or desire to commit a crime, but because of the influence of Aethanol throughthe alcohol he drinks, it causes that person to commit a crime.